An optimized algorithm for association rule hiding technique using Hybrid Approach - Joshi, Apoorva; Gautam, Pratima (International Journal of Computer Sciences and Engineering, 2019)
Data mining is basically a process of identifying different patterns from huge amount of data. Association rule hiding technique target to find out dependency relationships transversely attributes. It may reveal sensitive information. With widespread applications of data mining techniques to diverse domains, privacy preservation becomes compulsory. Association rule hiding is one of the important techniques of privacy preserving data mining to keep the sensitive association rules generated by association rule mining. In this paper we talk about heuristic approach for hiding sensitive rules. The proposed technique provides us solution of privacy disclosure and hides the sensitive rules.